In planta complementation of the betalain biosynthetic pathway with a bacterial dioxygenase. - María Alejandra Guerrero-Rubio; Hester Sheehan; Samuel F Brockington (PLoS ONE)
Betalains are pigments naturally produced by plants belonging to the order Caryophyllales. However, 4,5-L-DOPA-extradiol-dioxygenase (DODA), the main enzyme in their biosynthetic pathway, has also been characterized in other kingdoms including fungi or bacteria. These enzymes show few similarities with the plant enzymes at structural or kinetic levels but achieve the same activity, raising questions on their possible exchange with plant DODA enzymes and subsequent complementation in the biosynthetic pathway of betalains. In this work, we show that the DODA enzyme from the bacterium Gluconacetobacter diazotrophicus is able to provide the activity of L-DOPA dioxygenase and produce betalamic acid and betalains, in planta. Betalains were detected after transient expression of the genes required for their synthesis in the plant model Nicotiana benthamiana. HPLC-ESI-MS analysis showed that the expression of the bacterial enzyme gave rise to multiple betalains in a similar manner to plant DODAs, with vulgaxanthin I being the main pigment obtained in infiltrated leaves. Our results show that fully functional betalamic-forming enzymes from outside of the plant kingdom are able to complement the plant-based betalain biosynthetic pathway. This supports the proposition of convergent evolution of enzymes with betalain-forming activity, not only within Caryophyllales, but also in other kingdoms.